2023
DOI: 10.3390/systems11050246
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Review of NIMBY Conflict: Characteristics, Mechanism and Evolution Simulation

Abstract: In the process of modernization and urbanization, some government projects or facilities with negative externalities have caused the psychology of residents nearby to “Not in My Backyard” (NIMBY). That is, adopting strong and resolute, sometimes highly emotional collective opposition or even resistance behavior. This triggered a NIMBY conflict. From the perspective of Complexity, this study re-examines the characteristics and evolution mechanism of NIMBY conflict and draws the following conclusions: (1) NIMBY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The problem of changing neighbourhoods and adaptive difficulties became apparent with the rise of the NIMBY (Not in My Backyard) movement. Studies have shown that how one responds is significantly more important than how long it takes to respond to conflict [96]. Orchowska proposes an approach to redefining residential space that preserves emotional values, creative intentions of modernized areas, and semantic values [97].…”
Section: Discussionmentioning
confidence: 99%
“…The problem of changing neighbourhoods and adaptive difficulties became apparent with the rise of the NIMBY (Not in My Backyard) movement. Studies have shown that how one responds is significantly more important than how long it takes to respond to conflict [96]. Orchowska proposes an approach to redefining residential space that preserves emotional values, creative intentions of modernized areas, and semantic values [97].…”
Section: Discussionmentioning
confidence: 99%